'Nobler imaginings and mightier struggles' : Octavia Hill, social activism and the remaking of British society - Baigent, Elizabeth; Cowell, Ben (Institute of Historical Research, 2016)
"This volume reassesses the life and work of Octavia Hill, housing reformer, open space campaigner, co-founder of the National Trust, founder of the Army Cadet Force, and the first woman to be invited to sit on a royal commission. In her lifetime she was widely regarded as an authority on a broad range of social problems. Yet despite her early pre-eminence, and the remarkable success of the institutions which she helped to found, Hill fell from public favour in the twentieth century. This book provides a nuanced portrait of Hill and her work in a broader context of social change, reflecting recent scholarship on nineteenth-century society in general, and on philanthropy and preservation, and women's role in them, in particular."--Back cover.